New records of phytoplankton for Bangladesh. 3. Volvocales - Khondker, Moniruzzaman; Bhuiyan, Rauf Ahmed; Yeasmin, Jenat; Alam, Munirul; Sack, R. Bradley; Huq, Anwar; Colwell, Rita R (Bangladesh Journal of Plant Taxonomy, 2007)
This study presents 21 species of Chlamydomonas, four species of Carteria, two species of each of Nephroselmis, Pyramidomonas and Scherffelia, and Collodictyon triciliatum, Polytoma minus, Tetrachloridium ? allorgei and Tetraselmis cordiformis. These species have been reported from some ponds of Mathbaria of Pirojpur and Bakerganj of Barisal districts in Bangladesh. Key words: Phytoplankton, New records, Bangladesh, Volvocales, Ponds DOI: 10.3329/bjpt.v14i1.518 Bangladesh J. Plant Taxon. 14(1): 1-12, 2007 (June)